Feline Infectious Peritonitis (FIP): A Case Report - Panasantikul, Kesorn; Kleangkaew, Auriwan; Rungpupradit, Jetsada (Journal of Mahanakorn Veterinary Medicine, 2022)
A male Munchkin cat was brought to a small animal teaching hospital at Mahanakorn University of Technology. The patient presentation with vomiting, chronic diarrhea, and intermittent fever. From history-taking, the owner previously had a cat that was diagnosed with feline infectious peritonitis (FIP) living in the same house but had isolated in a separate area. Fecal examination revealed bacterial enteritis. Hematology and blood chemistry results shown lymphopenia, hypoalbuminemia, and low serum albumin/globulin ratio (0.3 A: G ratio). Abdominal ultrasound revealed mesenteric lymph node (MLN) enlargement and cholecystitis. Cell cytology from the liver and MLN revealed suppurative inflammation. Reverse transcription PCR (RT-PCR) was negative for the Feline coronavirus (FCoV) in the blood sample. On the 4th day of treatment, the cat developed pleural and peritoneal effusion. Thoracentesis and abdominocentesis were performed and submitted for analysis. The fluid’s results were classified as modified transudate, low A: G ratio (0.3), Rivalta’s test (positive), and positive for FCoV by using RT-PCR. On the 8th day of treatment, the cat died from systemic hypotension. Viscous straw yellow-colored fluid and pyogranulomatous lesions at the liver, lung, kidney, and MLN were observed from the necropsy. Histopathology’s results shown severe suppurative inflammation in all the above organs. FIP was confirmed by detected FCoV antigen in the cytoplasm of macrophages in the kidney and lung tissue by immunohistochemistry staining.